Demokratisasi Internal Partai Politik di Indonesia Dalam Proses Rekrutmen Calon Kepala Daerah - Zieyad Alfeiyad Ahfi (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2023)
In modern democracies, political parties are the means of connecting people with government. The existence of political parties is mandatory because it is a forum for public participation to exercise their political rights in becoming a candidate for leader. This paper analyzes the internal democratization of political parties in Indonesia in the recruitment process for candidates for regional heads. This research is a normative legal research using primary, secondary and non-legal sources. The finding of this study is that in the recruitment process for candidates for regional heads, there is still a process that is not transparent so that it is not participatory. This is because of the privillege owned by political parties as a mandatory democratic facility and the high cost of politics so that political parties apply unwritten rules, namely political dowry. There are two solutions that the author offers to decide the problem of political dowry, namely: First, provisions regarding the recruitment of candidates for regional heads must not be fully given to political parties, second, political financing must be re-regulated, lest any personal money enter the politics.